Genetic diversity of Faidherbia albida (Del.) A. Chev accessions held at the World Agroforestry Centre - Kithurea, Robert K.; Muchugia, Alice; Jamnadassa, Ramni; Njoka, Fredrick M.; Mwauraa, Lucy (Taylor & Francis, 2015)
This study assessed the extent and distribution of genetic diversity of 29 Faidherbia albida provenances from 10 African countries by employing amplified fragment length polymorphism with an aim of providing crucial genetic diversity information for in situ and ex situ management and utilization of the collections. Plant materials consisted of F. albida accessions held at World Agroforestry Centre [International Center for Research in Agroforestry (ICRAF)] seed bank. A total of 676 bands ranging from 50 to 499 base pairs were scored using five primer sets. The average percentage of polymorphic loci over all populations was 31.7. The collection from the Taveta (Kenya) provenance had the highest percentage of polymorphic loci (69.5%), while those from Manapools (Zimbabwe) had the lowest (13.5). The average heterozygosity ranged from 0.05 to 0.28 with a mean of 0.16 across all the provenances. There was high and quite significant population differentiation among the populations (PhipT ¼ 0.64, p ¼ 0.001). Analysis of molecular variance revealed that 64% of the total variation was partitioned among the populations and 36% within the populations. Unweighed pair-group method with arithmetic averaging clustering generally reflected the geographical origins and similarity of the germplasm except West African provenances indicating complex evolutionary trends that have shaped the population structure and distribution of the species. The results show that the germplasm held at ICRAF seed bank is of low genetic variability with the western and some of the eastern Africa provenances having the highest diversity. More collections need to be done to cover the entire distribution range of this species to capture more diversity and enrich this gene pool.
DOI:10.1080/14728028.2015.1054439
Keywords: amplified fragment length polymorphism; Genetic diversity; Faidherbia albida; germplasm conservation; heterozygosity; provenances; population differentiation